Understanding the role of sex on outcomes for the cancer patient undergoing treatment with immune checkpoint inhibitors: a scoping review protocol - Grace Lu-Yao; Jennifer M Johnson; Amy L Shaver; Nikita Nikita; Swapnil Sharma; Daniel S Lefler; Atrayee Basu-Mallick; Meghan L Butryn (BMJ Open)
Introduction Immune checkpoint inhibitors (ICIs) have changed the treatment landscape for multiple cancer types. Sex plays an important role in both the development of cancer as well as the functioning of the immune system. Though a difference in response to immune therapy is emerging between men and women it is unclear how this difference affects cancer outcomes and what the potential underlying mechanisms are for those effects. The objective of this study is to describe the influence that sex has on the outcomes experienced by cancer patients on ICI therapy and to identify and analyse any knowledge gaps in the field.Method and analysis The framework for this methodology was guided by the Joanna Briggs Institute Manual for Evidence Synthesis. The search and review will be conducted from January 2022 to June 2022. Two independent researchers will screen titles and abstracts followed by full-text screening for manuscript inclusion. Full length studies published between 2010 and December 2021 found in PubMed, Cochrane, CINAHL, and Scopus describing the influence of sex differences on cancer outcomes in patients treated with ICIs will be included. After data are extracted it will be summarised for presentation.Ethics and dissemination The findings of this scoping review will be published in a peer-reviewed journal. The results will be used to inform future studies on the potential differential impacts of ICIs. All data are from published openly accessible sources and therefore no ethical clearance is necessary.